Differences between feelings, emotions and desires in terms of interactive quality - Cookson, Lawrence James (Advances in Social Sciences Research Journal, 2015)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-AU; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The importance of interactive quality has become central to understanding the meaning of wildness, the natural state. This article examines the differences between feelings, emotions and desires according to their roles during interaction. Emotions and desires are placed on the engaging side of the interactive loop, while feelings register the feedback gained from interaction. Feelings are further divided into somatic and neocortical feelings, where somatic feelings such pain and hunger register how the body is being affected, while neocortical feelings are based upon the pleasure or displeasure for how a constructed sense of fairness and personal context was affected. Desires are thought to arise directly from bodily organs and from a <span style="color: black; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-AU; mso-fareast-language: EN-AU; mso-bidi-language: AR-SA;">theorised neocortical ‘interaction desire’ that seeks parsimony within the organisation of its developing pathways. The production of emotions is influenced by the level of wildness or ease of interaction being experienced within a given environment, so that they become more prevalent, varied and extreme during conditions of difficulty and conflict.